2011
DOI: 10.18357/ijcyfs21/220115427
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Examination of the Relationship Between Childhood Neglect and Juvenile Delinquency in the Cambridge Study in Delinquent Development

Abstract: Abstract:The relationship between childhood neglect and later life outcomes is an understudied topic. This study employs data from the Cambridge Study in Delinquent Development, a longitudinal follow-up of 411 working-class males in London, to examine (a) the profiles of the boys who were neglected in childhood and (b) the relationship between childhood neglect and juvenile delinquency, controlling for other risk factors. Findings reveal that boys who were neglected in childhood were characterized by other adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Finally, despite the importance of early detection and intervention in cases of child abuse and neglect, there may be unintended consequences of early identification. The fact that neglect and other risk factors measured in childhood are better predictors of officially recorded crime when compared to self‐reports suggests the presence of stigmatization effects (Kazemian et al., ). In their study of the intergenerational transmission of abuse and neglect (Widom et al., ), among parents who reported engaging in and among offspring who reported being the victim of child abuse and/or neglect, those whose parents had official histories of maltreatment were more than two times as likely to have a CPS report than those without those official histories, suggesting a detection or surveillance bias.…”
Section: Implications For Practicementioning
confidence: 99%
“…Finally, despite the importance of early detection and intervention in cases of child abuse and neglect, there may be unintended consequences of early identification. The fact that neglect and other risk factors measured in childhood are better predictors of officially recorded crime when compared to self‐reports suggests the presence of stigmatization effects (Kazemian et al., ). In their study of the intergenerational transmission of abuse and neglect (Widom et al., ), among parents who reported engaging in and among offspring who reported being the victim of child abuse and/or neglect, those whose parents had official histories of maltreatment were more than two times as likely to have a CPS report than those without those official histories, suggesting a detection or surveillance bias.…”
Section: Implications For Practicementioning
confidence: 99%
“…Exposure to physical and emotional neglect in childhood can lead to biological, cognitive, and interpersonal deficits in childhood and early adolescence which lay the foundation for psychological distress in early adulthood (Hildyard & Wolfe, 2002; Kazemian, Widom, & Farrington, 2011; Sheridan & McLaughlin, 2014) To date, however, the majority of maltreatment, let alone neglect research, has ignored the developmental period between adolescence and adulthood leaving it unclear what the specific relation between neglect and psychological functioning is during this developmental stage (Schulenberg, Sameroff, & Cicchetti, 2004; Toth & Cicchetti, 2013). Due to the complex relation between maltreatment experiences and other risk and protective factors, it is reasonable to expect that distinct developmental stages may forecast specific manifestations of resilience and distress as one copes with developmentally-salient challenges across the lifespan (Cicchetti & Toth, 1995; Mersky & Topitzes, 2010).…”
Section: The Distal Consequences Of Physical and Emotional Neglect Inmentioning
confidence: 99%
“…A recent study showed that boys who were victim of childhood neglect were four times more often convicted for offending than juveniles who were not victim of childhood neglect (Kazemian et al . ).…”
Section: Introductionmentioning
confidence: 97%